2021
DOI: 10.15388/amed.2021.28.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Phenomena of Disseminated Intravascular Coagulopathy in Hepatic Angiosarcoma – Rare, Challenging and Fatal. Case Report and Literature Review

Abstract: Background. Hepatic angiosarcoma is an uncommon, malignant, primary liver tumor, comprising 2% of liver cancers and accounting for < 1% of all sarcomas. Patients usually present with nonspecific symptoms, such as fatigue, weight loss, right upper quadrant pain, anemia, which leads to late diagnosis of an advanced stage tumor. The median life expectancy after the diagnosis of hepatic angiosarcoma is about 6 months, with only 3% of patients surviving more than 2 years. Liver failure and hemoperitoneum are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Studies have reported that PHA is closely related to D-dimer and platelet levels, manifesting as increased D-dimer levels and thrombocytopenia. Physiological conditions caused by malignant endodermic cells can promote platelet adhesion and activation, leading to the excessive consumption of platelets and coagulation factors at the tumor site[ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that PHA is closely related to D-dimer and platelet levels, manifesting as increased D-dimer levels and thrombocytopenia. Physiological conditions caused by malignant endodermic cells can promote platelet adhesion and activation, leading to the excessive consumption of platelets and coagulation factors at the tumor site[ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…PHA progresses rapidly, with extrahepatic metastasis occurring in half of patients at the time of discovery, the most common sites of metastasis in PHA are the spleen, lungs and bone[ 16 ]. Intrasplenic metastasis are rarer, so it provides favorable diagnostic clues for the diagnosis of PHA[ 17 - 19 ].…”
Section: Discussionmentioning
confidence: 99%